2019
DOI: 10.1002/mabi.201900206
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Foreign Body Reaction against PDMS Implant by Grafting Topographically Different Poly(acrylic acid) Micropatterns

Abstract: The surface of poly(dimethylsiloxane) (PDMS) is grafted with poly(acrylic acid) (PAA) layers via surface‐initiated photopolymerization to suppress the capsular contracture resulting from a foreign body reaction. Owing to the nature of photo‐induced polymerization, various PAA micropatterns can be fabricated using photolithography. Hole and stripe micropatterns ≈100‐µm wide and 3‐µm thick are grafted onto the PDMS surface without delamination. The incorporation of PAA micropatterns provides not only chemical cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…These findings may help in uncovering new therapeutic targets for prevention and intervention of ePTFE-related complications [ 30 ]. For example, we found that both innate and adaptive immune responses might be involved in the ePTFE-related adverse reactions, which extended previous observations that only innate immune responses existed in FBR caused by artificial material implantation [ 17 , 19 , 44 , 45 ]. Many molecules and signal pathways were involved in the mechanisms underlying the ePTFE-related adverse reactions, and they might interact with each other in multiple ways, which increased the difficulty of learning the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings may help in uncovering new therapeutic targets for prevention and intervention of ePTFE-related complications [ 30 ]. For example, we found that both innate and adaptive immune responses might be involved in the ePTFE-related adverse reactions, which extended previous observations that only innate immune responses existed in FBR caused by artificial material implantation [ 17 , 19 , 44 , 45 ]. Many molecules and signal pathways were involved in the mechanisms underlying the ePTFE-related adverse reactions, and they might interact with each other in multiple ways, which increased the difficulty of learning the underlying mechanisms.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, many efforts have tried to improve the anticoagulant properties of ePTFE and they include heparin coating [1], endothelial cell coverage [6], antibody or peptide coating the ePTFE [11][12][13], and others [14,15]. Similarly, several methods have been developed to prevent intimal hyperplasia or inhibit the FBR [16][17][18][19]. However, their efficacy and stability are unsatisfactory and far away from clinical application [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…PDMS was prepared by mixing the base and curing agent at 10:1 (w/w), which was reported as the best ratio for biological application 46 , 47 and has been used as a model of silicone implants in several studies. 48 , 49 , 50 , 51 , 52 We chemically modified the surface of PDMS with 150 mM IA (Figure 1 ). This concentration was selected because previously, it was reported to result in the excellent enhancement of biocompatibility and reduction in capsular contracture formation of the PDMS surface, similar to results with the 0.50 wt% IA‐GT polymer but with an easier preparation method than the latter.…”
Section: Resultsmentioning
confidence: 99%
“…These results were consistent with those of previous studies, which showed that hydrophilic surfaces were better at preventing protein adsorption than hydrophobic surfaces. 21 , 50 , 59 , 60 Figure 2d shows cell cytotoxicity results using the 3‐[4,5‐dimethylthiazol‐2‐yl]‐2,5‐diphenyltetrazolium bromide (MTT) assay. The PDMS and IA‐PDMS samples showed significantly lower absorbance than cells on a plate at Days 1, 3, and 7 ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Three types of drugs that inhibit the FBR include glucocorticoids, anti-fibrotic agents, and gene silencing 55 . First, glucocorticoids are widely adopted drugs which serve as a regulator of the inflammatory reaction 56 . Glucocorticoids target immune cells, which are associated with the FBR, including macrophages, neutrophils, and lymphocytes.…”
Section: Drug Delivery Drugmentioning
confidence: 99%